Detection of Cd69 Marker by Flow Cytometry in Iraqi Patients with Coeliac Disease. - Al-Sakini, Karrar A.; Al-hadithi, Hayfaa S.; Asker, Bassim A. (Journal of the Faculty of Medicine Baghdad, 2014)
J Fac Med Baghdad 2014; Vol.56, No .2 Received Feb .2014 Accepted Apr. 2014 Background: Coeliac disease is a chronic, immunologically determined form of enteropathy affecting the small intestine in genetically predisposed children and adults. It is precipitated by the ingestion of gluten-containing foods. It is also referred to as celiac sprue, gluten-sensitive enteropathy, or nontropical sprue. CD69 is a lymphoid activation antigen whose rapid expression makes it suitable for the detection of T-cell activation and for subset activation analyses. Objective: Investigate the clinical value of using CD69 marker in diagnosis of coeliac disease. Patients and method: A total of 40 patients (21 males & 19 females) with coeliac disease attending the Gastroenterology and Hepatology Teaching Hospital in the Medical City, during the period between February 2013 and June 2013.The control group consisted of 40 apparently healthy individuals who were not complaining of any gastro-intestinal problem. Venous blood samples were taken from each subject (fresh blood tested for detection of CD69 marker by flow cytometry). Results: The age of coeliac disease patients in this study was ranged between (2-56) years with the mean age of (15.6 ± 13.1) years. Blood level of CD69 positive T-lymphocytes was significantly increased in cases group when compared with controls group. Conclusion: Detection of CD69 marker is an accurate and rapid method for diagnosis of coeliac disease.